New Perspectives on Old and New Therapies of Staphylococcal Skin Infections: The Role of Biofilm Targeting in Wound Healing - Oriana Simonetti (MDPI AG, 2021)
Among the most common complications of both chronic wound and surgical sites are staphylococcal skin infections, which slow down the wound healing process due to various virulence factors, including the ability to produce biofilms. Furthermore, staphylococcal skin infections are often caused by methicillin-resistant Staphylococcus aureus (MRSA) and become a therapeutic challenge. The aim of this narrative review is to collect the latest evidence on old and new anti-staphylococcal therapies, assessing their anti-biofilm properties and their effect on skin wound healing. We considered antibiotics, quorum sensing inhibitors, antimicrobial peptides, topical dressings, and antimicrobial photo-dynamic therapy. According to our review of the literature, targeting of biofilm is an important therapeutic choice in acute and chronic infected skin wounds both to overcome antibiotic resistance and to achieve better wound healing.